ERP System Selection Analysis Using the Analytical Hierarchy Process (AHP): A Case Study of an Automotive Manufacturing Company - Abdul Sidik; Riri Satria; Irhanas Hanafi Rahmat; Bimo Iman Smartadi; Christine Cecylia Munthe (Green Publisher Indonesia, 2026)
PT XYZ is an automotive component manufacturer facing a 15% data mismatch between production reports and inventory data. This issue has led to a 62% increase in operational costs, 12% product delivery delays, and a 40% risk of customer contract fines. To overcome these challenges, the company plans to implement an ERP system to improve data accuracy and operational efficiency. However, the main challenge remains determining which ERP system best suits the company's business need. This research aims to provide recommendations for the right ERP system for PT XYZ using the Analytical Hierarchy Process (AHP) method. This approach involved interviews with Inventory Supervisors, Finance Managers, Production Managers, and Business Directors, as well as analysis of criteria that have been validated through literature studies. AHP is used to prioritize key criteria, namely Ease of Use, Price, Adaptability, Scalability, and Time on the Market, and evaluate four ERP alternatives, namely Odoo Enterprise, SAP, Microsoft Dynamics, and Infor Cloudsuite. The results of the study show that Odoo Enterprise was chosen as an ERP system that is pal-ing according to the needs of PT XYZ. This selection is based on priority calculations using AHP with a consistency level of 0.07, which shows results that are valid enough to support decision-making. The implementation of the right ERP system is expected to be able to solve the problem of asynchronous data, support operational efficiency, sustainable business growth, and increase customer trust in PT XYZ.